Acute pancreatitis due to hepatitis B virus. A case report - Duarte Calderón, Camilo Andrés (2022)
Acute pancreatitis is an inflammatory condition that is related to various etiologies. However, an infrequent one is acute infection by hepatotropic viruses. We present the case of a 33-year-old man who consulted the emergency department for abdominal pain and generalized jaundice. Serological studies reported acute infection by Hepatitis B Virus; The patient was managed with clinical and paraclinical monitoring of liver function tests together with supportive therapy with dextrose. The patient persisted with increasing abdominal pain and cholestasis, so they were considered differential. Magnetic resonance imaging of the upper abdomen showed acute non-biliary pancreatitis that was concluded secondary to the infectious process due to hepatitis B after ruling out other causes. The patient did not require changes in management with improvement in liver function tests, so he was discharged from hospital with favorable evolution in outpatient follow-up. Acute pancreatitis secondary to Hepatitis B Virus is a pathology that should be suspected and studied when the patient's clinical picture does not show improvement; Diagnosis is based on measurement of pancreatic enzyme levels.